Relevance of Teacher Personality Characteristics According to Imam al-Ghazali with the Director General of GTK Regulation Number 2626 of 2023 Regarding the Teacher Competency Model - Ahmad Dawam Lutfi; Abdul Ghofur; Ainurrafiq (Journal of Practice Learning and Educational Development, 2025)
Teachers are required to have a well-rounded personality because they serve as role models for students. Teacher personality is one of the four core competencies, alongside pedagogical, professional, and social competencies. Teachers play a crucial role in shaping students who are not only intellectually capable but also spiritually mature. This study examines the thoughts of Imam al-Ghazali on teacher personality and relates them to the Indonesian teacher personality competency standards as stipulated in the Director General of Teacher and Education Regulation Number 2626 of 2023 concerning the Teacher Competency Model. Using a qualitative library research approach, this study analyzes Imam al-Ghazali’s views in Ihya Ulumuddin, particularly in the chapter al-Mu’allim wa al-Muta’allim. The results indicate that Imam al-Ghazali’s eight duties and obligations of teachers are highly relevant to the current teacher personality competency standards. This study concludes that teacher personality competence is essential, especially in the era of rapid technological and social change, since students naturally imitate their teachers’ behavior.